2012
DOI: 10.1016/j.neuron.2012.03.032
|View full text |Cite
|
Sign up to set email alerts
|

BAD-Dependent Regulation of Fuel Metabolism and KATP Channel Activity Confers Resistance to Epileptic Seizures

Abstract: Summary Neuronal excitation can be substantially modulated by alterations in metabolism, as evident from the anticonvulsant effect of diets that reduce glucose utilization and promote ketone body metabolism. We provide genetic evidence that BAD, a protein with dual functions in apoptosis and glucose metabolism, imparts reciprocal effects on metabolism of glucose and ketone bodies in brain cells. These effects involve phospho-regulation of BAD and are independent of its apoptotic function. BAD modifications tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
164
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(174 citation statements)
references
References 64 publications
(93 reference statements)
8
164
2
Order By: Relevance
“…Aside from ␤-cells, neurons in the central nervous system involved in a wide range of physiological and pathological processes, including energy homeostasis (18,(61)(62)(63), epilepsy (64,65), and Parkinson disease (66), express K ATP channels and are subjected to regulation by leptin and metabolic signals. Thus, the K ATP channel regulatory mechanism identified here may extend well beyond pancreatic ␤-cells, with broad implications in metabolic regulation in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from ␤-cells, neurons in the central nervous system involved in a wide range of physiological and pathological processes, including energy homeostasis (18,(61)(62)(63), epilepsy (64,65), and Parkinson disease (66), express K ATP channels and are subjected to regulation by leptin and metabolic signals. Thus, the K ATP channel regulatory mechanism identified here may extend well beyond pancreatic ␤-cells, with broad implications in metabolic regulation in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from implications in treating congenital hyperinsulinism caused by trafficking-impaired K ATP channels with SUR1 TMD0 mutations, the finding that carbamazepine has additional targets than previously appreciated has implications for its clinical use for the treatment of approved diseases. It is worth noting that aside from their well established role in regulating hormone secretion K ATP channels are also widely expressed in the brain and have been implicated in epilepsy (68,69). Whether the clinical effect of carbamazepine as an anticonvulsant is related in part to an effect on K ATP channels in the central nervous system is an interesting issue to address in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, multiple studies have demonstrated elevated antioxidant activity, diminished production of ROS, and decreased ROS-induced damage with the KD ( 6,14,94 ). Figure 3 summarizes the substrates and pathways linking mitochondrial redox changes to the TCA and astrocytes from Bad Ϫ / Ϫ or Bad S155A mice exhibited reduced mitochondrial oxidative metabolism of glucose, but enhanced mitochondrial respiration in the presence of BHB ( 87 ). Interestingly, this change in metabolism was implicated in neuronal excitability, as Bad Ϫ / Ϫ or Bad S155A mice also demonstrated increased resistance to KA-and PTZinduced seizures, effects that required the opening of K ATP channels ( 87 ).…”
Section: Bioenergetic and Mitochondrial Changesmentioning
confidence: 99%
“…Figure 3 summarizes the substrates and pathways linking mitochondrial redox changes to the TCA and astrocytes from Bad Ϫ / Ϫ or Bad S155A mice exhibited reduced mitochondrial oxidative metabolism of glucose, but enhanced mitochondrial respiration in the presence of BHB ( 87 ). Interestingly, this change in metabolism was implicated in neuronal excitability, as Bad Ϫ / Ϫ or Bad S155A mice also demonstrated increased resistance to KA-and PTZinduced seizures, effects that required the opening of K ATP channels ( 87 ). While K ATP channel opening induced by low ATP levels is indeed an intriguing mechanism that couples the metabolic state of the cell to neuronal excitability, the fact that the KD and ketone bodies actually increase ATP production needs to be reconciled with the K ATP channel hypothesis ( 84,88,89 ).…”
Section: Bioenergetic and Mitochondrial Changesmentioning
confidence: 99%